THE PLANET BEYOND THE PLUME HYPOTHESIS - Smith A.D.; Lewis C. (My University, 1999)
Acceptance of the theory of plate tectonics was accompanied by the rise of the mantle plume/hotspot concept which has come to dominate geodynamics from its use both as an explanation for the origin of intraplate volcanism and as a reference frame for plate motions. However, even with a large degree of flexibility permitted in plume composition, temperature, size, and depth of origin, adoption of any limited number of hotspots means the plume model cannot account for all occurrences of the type of volcanism it was devised to explain. While scientific protocol would normally demand that an alternative explanation be sought, there have been few challenges to “plume theory” on account of a series of intricate controls set up by the plume model which makes plumes seem to be an essential feature of the Earth. The hotspot frame acts not only as a reference but also controls plate tectonics. Accommodating plumes relegates mantle convection to a weak, sluggish effect such that basal drag appears as a minor, resisting force, with plates having to move themselves by boundary forces and continents having to be rifted by plumes. Correspondingly, the geochemical evolution of the mantle is controlled by the requirement to isolate subducted crust into plume sources which limits potential buffers on the composition of the MORB-source to plume- or lower mantle material. Crustal growth and Precambrian tectonics are controlled by interpretations of greenstone belts as oceanic plateaus generated by plumes. Challenges to any aspect of the plume model are thus liable to be dismissed unless a counter explanation is offered across the geodynamic spectrum influenced by “plume theory”. Nonetheless, an alternative synthesis can be made based on longstanding petrological evidence for derivation of intraplate volcanism from volatile-bearing sources (wetspots) in conjunction with concepts dismissed for being incompatible or superfluous to “plume theory”. In the alternative Earth, the sources for intraplate volcanism evolve from the source residues of arc volcanism located along sutures in the continental mantle. Continental rifting and the lateral distribution of intraplate sources in the asthenosphere are controlled by Earth rotation. Shear induced on the base of the asthenosphere from the mesosphere as the Earth rotates is transmitted to the lithosphere as basal drag. Attenuation of the drag due to the low viscosity of the asthenosphere, in conjunction with plate motions from boundary forces, results in a rotation differential of up to 5 cm yr−1 between the lithosphere and mesosphere manifest as westward plate lag/eastward mantle flow. Continental rifting results from basal drag supplemented by local convection induced by lithospheric architecture. Large continental igneous provinces are generated by convective melting, with passive margin volcanic sequences following the axis of rifting and flood basalts overlying the intersection of sutures in the continental mantle. As rifting progresses, the convection cells expand, cycling continental mantle from sutures perpendicular to the rift axis to generate intraplate tracks in the ocean basin. Continental mantle not melted on rifting, or delaminated on continental collision, becomes displaced to the east of the continent by differential rotation, which also sets up a means for tapping the material to give fixed melting anomalies. When plates move counter to the Earth's rotation, as in the example of the Pacific plate, asthenospheric flow is characterised by a counterflow regime with a zero velocity layer at depths within the stability field for volatile-bearing minerals. Intraplate volcanism results when melts are tapped from this stationary layer along lithospheric stress trajectories induced by stressing of the plate from variations in the subduction geometry around the margins of the plate. Plate boundary forces acting in the same direction as Earth rotation, as for the Nazca plate, produce fast plate velocities but not counterflow, though convergent margin geometry may still induce propagating fractures which set up melting anomalies. Lateral migration of asthenospheric domains allows the sources of Pacific intraplate volcanism to be traced back to continental mantle eroded during the breakup of Gondwana and the amalgamation of Asia in the Paleozoic. Intraplate volcanism in the South Pacific therefore has a common Gondwanan origin to intraplate volcanism in the South Atlantic and Indian Oceans, hence the DUPAL anomaly is entirely of shallow origin. Such domains constitute a second order geochemical heterogeneity superimposed on a streaky/marble-cake structure arising from remixing of subducted crust with the convecting mantle. During the Proterozoic and Phanerozoic, remixing of slabs has buffered the evolution of the depleted mantle to a rate of 2.2 εNd units Ga−1, with fractionation of Lu from Hf in the sediment component imparting the large range in relative to observed in MORB. Only the high εNd values of some Archean komatiites are compatible with derivation from unbuffered mantle. The existence of a very depleted reservoir is attributed to stabilisation of a large early continental crust through either obduction tectonics or slab melting regimes which reduced the efficiency of crustal recycling back into the mantle. Generation of komatiite is therefore a consequence of mantle composition, and is permitted in ocean ridge environments and/or under hydrous melting conditions. Correspondingly, as intraplate volcanism depends on survival of volatile-bearing sources, its appearance in the Middle Proterozoic corresponds to the time in the Earth's thermal evolution at which minerals such as phlogopite and amphibole could survive in off-ridge environments in the shallow asthenosphere. The geodynamic evolution of the Earth was thus determined at convergent margins, not by plumes and hotspots, with the decline in thermal regime causing both a reduction in size of crust and continental mantle roots, the latter becoming a source for intraplate volcanism while the crust was incorporated into the convecting mantle.
Keywords: Paleozoic; Proterozoic; Precambrian; Archean; Paleozoic; Precambrian::Proterozoic; Precambrian; Precambrian::Archean; Палеозой; Докембрий; Докембрий::Протерозой; Докембрий::Архей